Impact of Using the Self-Study Guide to Reduce the Negative Effects of Teachers’ Turnover on Students’ Performance: a Study Conducted in a Private American School in Abu Dhabi - FARAHAT, NESRINE (2019)
This work proposes a novel Self-Study Guide that can be used in high schools suffering from frequent Teachers’ Turnover during the academic year. Teachers Turnover is a global escalating problem with some teachers decide to leave their schools or change career during the school year. In this study, I have assessed the feasibility of applying the Self-Study Guide in a private high school in United Arab Emirates (UAE). Three groups of students have been recruited for the study with each group guided to study with a different technique. A mixed-approach (quantitative- qualitative) is used to detect the success of using the proposed Guide to solve the Turnover problem. Firstly, the study presents factors and consequences of Teachers’ Turnover with previously suggested solutions in case no qualified teachers are found. Secondly, it investigates how schools and educational institutes deal with turnover problems. Thirdly, it presents the key theories that helped the researcher frame her study: such as Culture Exchange Theory, Social Development Theory, Motivation Theory, Constructivism Theory, Collaborative Learning Theory and Creativity Theory. Finally, it presents a new program called a Self-Study Guide as a solution for the Turnover problem. To measure the validity and significance of the Self-Study Guide program, a comparison of students’ academic performance is conducted among 3 groups of students who learned a certain lesson through different techniques. Another comparison, to measure students’ motivation towards learning, is conducted within one group of students only, who learn 3 different lessons using the three different techniques. This study aims at examining the significance of the Self-Study Guide on the level of performance, level of motivation and creativity of students in learning. It, also, recommends directions for future studies. Results show that students’ best performance is recorded in the teacher-supported group with a 100 % success rate, while 90 % success rate is found within the Study-Guide’s group and 75 % success rate for students who studied completely independent. The Self-Study guide proposed in this research is found to have a significant positive impact on student’s level and academic performance with possible teachers’ turnover during the school year.